Analisis Ketidakpastian Lingkungan, Sistem Informasi Akuntansi Manajemen, Dan Kualitas Informasi Akuntansi Manajemen Terhadap Proses Pengambilan Keputusan - Azwani Aulia (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2020)
In this global era, environmental uncertainty is a challenge for a company in running its business. Therefore, management accounting information for companies is useful for providing analytical tools both qualitative and quantitative as a reference in management decision making. In this case, the use of management accounting information is used as a reference in making decisions. Managers who need this information are then processed into accurate management accounting information. This study aims to analyze how much influence environmental uncertainty, management accounting information systems, and the quality of management accounting information on the quality of management accounting information, on the decision-making process in the food industry in Bandung. The analysis method used is path analysis. Based on the results of the study, it is found that environmental uncertainty affects the quality of management accounting information and management accounting information systems and the quality of management accounting information also affects the decision making process in the food industry in Bandung.